CEO Power, Internal Control Quality, and Audit Committee Effectiveness in Substance Versus in Form - Lisic, Ling Lei; Neal, Terry L.; Zhang, Ivy Xiying; Zhang, Yan (Contemporary Accounting Research, 2016)
During the past decade, new regulations have been adopted to improve audit committee effectiveness. Prior research has generally provided evidence in support of these regulations and suggests that a more independent and expert audit committee is more effective. We posit that CEO power reduces or even eliminates the improvements in audit committee effectiveness resulting from independent and financially expert committee members. Thus, CEO power may result in an audit committee that appears effective in form but is not in substance. We construct a composite index for CEO power by combining ten CEO characteristics and employ the incidence of internal control weaknesses as a proxy for audit committee monitoring quality. Since all the firms in our sample have completely independent audit committees, we use financial expertise to examine the impact of CEO power on audit committee effectiveness. We find that, when CEO power is low, audit committee financial expertise is negatively associated with the incidence of internal control weaknesses. However, as CEO power increases, this association monotonically weakens. When CEO power reaches a sufficiently high level, this association is no longer negative. The moderating effect of CEO power on audit committee effectiveness is more prominent when the CEO extracts more rents from the firm through insider trading. Our results are not driven by the CEO 's involvement in director selection. Our paper suggests that more expert audit committees in form do not automatically translate into more effective monitoring. Rather, the substantive monitoring effectiveness of audit committees is contingent on CEO power.